Building youth leadership skills and community awareness: Engagement of rural youth with a community‐based leadership program. Issue 5 (6th January 2021) - T. Puxley, Shane; Chapin, Laurie A.
Abstract: Aims: Community leadership programs have the potential to positively impact many aspects of young people's development, as well as the community. This study, therefore,  aims to understand the experiences of the young people, particularly rural youth, involved with the Western Bulldogs Youth Leadership Project (WBYLP), a 7‐month program for Year‐9 and Year‐10 students, and if the developmental assets are a good framework to inform future program development. Method: A transformative mixed‐methods design was used and included surveys with 96 participants at two time points, and semistructured interviews with eight participants. Results: Quantitatively leadership significantly increased, particularly due to increases in the domains of understanding self and decision‐making skills. Social competencies increased, though total developmental assets did not. Interviews identified four primary themes: Perspective taking, self‐efficacy, community awareness, and decreased isolation. Conclusions: These results indicate that participants developed both individual skills relating to leadership and social skills. The participants also developed their awareness of the issues in their community.